The protective effects of lipoxin A4 on type 2 diabetes mellitus: A Chinese prospective cohort study - Wang, Sudan; Qian, Xiaoyan; Shen, Chao; Sun, Qian; Jing, Yang; Liu, Bingyue; Zhang, Kexin; Li, Mengyuan; Wang, Junrong; Zhou, Hui; Dong, Chen (Frontiers in Endocrinology, 2023)
Background: Several cellular and animal studies have suggested that lipoxin A4 (LXA4) has a protective effect on type 2 diabetes mellitus (T2DM) development. However, little is known about whether LXA4 influences T2DM development at the population level. Methods: We included 2755 non-diabetic participants from a cohort study in China who were followed for about seven years. Cox proportional hazards model was used to estimate hazard ratios (HRs) and 95% confidence intervals (CI) for the association between LXA4 and incident T2DM. Mediation models were used to examine how serum lipids as mediators impact the association between LXA4 and T2DM. Results: In total, 172 newly diagnosed T2DM cases were identified. Multivariate-adjusted HR for T2DM in the fourth compared with the first quartile of LXA4 was 0.62 (95% CI: 0.40-0.96). When used the optimal cutoff value determined by the receiver operating characteristic curve, the results showed participants with LXA4 > 2.84 ng/mL had a decreased T2DM risk compared to those with LXA4 ≤ 2.84 ng/mL (HR: 0.63, 95% CI: 0.45-0.89). The effect of LXA4 on incident T2DM was significantly modified by gender (P-interaction = 0.024) and family history of diabetes (P-interaction = 0.025). Additionally, the association between LXA4 and incident T2DM was partially suppressed by the TyG and TG/HDL-c ratio, with a suppression proportion of 22.2% and 16.0%, respectively. Conclusions: Higher LXA4 levels are significantly associated with a lower risk of T2DM development. The present findings would be helpful in understanding the effect of LXA4 on T2DM development at the population level.